Substituent, Temperature and Solvent Effects on the Keto-Enol Equilibrium in β-Ketoamides: A Nuclear Magnetic Resonance Study - Laurella, Sergio Luis (2013)
Substituent, temperature and solvent effects on tautomeric equilibria in several β-ketoamides have been investigated by means of nuclear magnetic resonance spectroscopy (NMR). Keto-enol equilibrium predominates over the amide-imidol one. The relative stability of the individual tautomers and the corresponding equilibrium shifts are explained consider- ing electronic and steric effects and tautomer stabilization via internal hydrogen bonds. In solution, these compounds exist mainly as ketoamide and Z-enolamide tautomers, both presenting intramolecular hydrogen bonds.